PERCEPTION AND OBSTACLES OF COLLEGE STUDENTS IN WRITING - Pande Agus Adiwijaya; Ni Made Ayu Purnami; I Wayan S Arsana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
This is a descriptive qualitative research which aimed at finding theperception and obstacles of college students in writing. The subject of this researchwas all of students in English Education Department of STKIP Suar Bangli inacademic year 2018/2019. There were three instruments used in this research,namely questionnaire, interview and documentation. From the data analysis it wasfound that students of English Education Department considered writing wasimportant for them and considered as the second most important skill afterspeaking. Teaching writing skill should be taught through the process of writing(drafting, writing and revising) in relax and fun situation with many practices. Theevaluation of writing should also provide feedbacks for their writing improvement.The most challenging obstacle that should be solved by the students was findingideas. The students also proposed some reasons that may trigger them to write suchas having idea/inspiration, having assignment, being in a good mood, there is timeallocation for writing, having motivation, and being in supportive situation andcondition. It is also suggested to teach writing skill by using project-based learningthrough proper process of writing starting from pre-writing, drafting, writing,revision and editing. The evaluation was also in form of portfolio assessment.